2021
DOI: 10.20944/preprints202107.0299.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation methods for Graphene, Metal and Polymer-based Composites for EMI Shielding Materials: State of the Art of Conventional and Machine Learning Methods

Abstract: The electromagnetic inference is an issue from decades, where working for a better shielding material is still on-going. The purpose of this study is to review the existing methods in the formation of graphene, metal and polymer-based composites. Study indicates that in graphene and metal-based composites, the utilization of alternating deposition method showed the highest shielding effectiveness, whereas, in polymer-based composite, the utilization of chemical vapor deposition method showed highest shielding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…For instance, the concentration of graphene, density of porous materials, amount of filler content and the thickness of the composite impacts an improvement in the shielding effectiveness. Before proceeding towards the method adaptation, it is important to have an in-dept understanding of the properties of the materials as well, as the authors discussed in [24]. Various studies showed that by increasing the graphene loading and composite thickness, at some extent the shielding effectiveness increases.…”
Section: Methods For Preparation Of Polymer-based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the concentration of graphene, density of porous materials, amount of filler content and the thickness of the composite impacts an improvement in the shielding effectiveness. Before proceeding towards the method adaptation, it is important to have an in-dept understanding of the properties of the materials as well, as the authors discussed in [24]. Various studies showed that by increasing the graphene loading and composite thickness, at some extent the shielding effectiveness increases.…”
Section: Methods For Preparation Of Polymer-based Compositesmentioning
confidence: 99%
“…This review aims to assess the various traditional and artificial intelligence methods to synthesize the shielding composites to deal with EMI. This paper builds on a previous review [24] conducted on the applications of graphene, iron and polymer composites in EMI shielding, where the top materials were highlighted in each frequency range to secure good shielding effectiveness. In this review preparation methods that help to build the EMI shielding composites have been reviewed.…”
Section: Introductionmentioning
confidence: 94%